Glyceraldehyde‐3‐phosphate dehydrogenase is regulated by ferredoxin‐NADP reductase in the diatom Asterionella formosa. Issue 2 (6th May 2014) - Mekhalfi, Malika; Puppo, Carine; Avilan, Luisana; Lebrun, Régine; Mansuelle, Pascal; Maberly, Stephen C.; Gontero, Brigitte
Summary: Diatoms are a widespread and ecologically important group of heterokont algae that contribute c . 20% to global productivity. Previous work has shown that regulation of their key Calvin cycle enzymes differs from that of the Plantae, and that in crude extracts, glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) can be inhibited by nicotinamide adenine dinucleotide phosphate reduced (NADPH) under oxidizing conditions. The freshwater diatom, Asterionella formosa, was studied using enzyme kinetics, chromatography, surface plasmon resonance, mass spectrometry and sequence analysis to determine the mechanism behind this GAPDH inhibition. GAPDH interacted with ferredoxin–nicotinamide adenine dinucleotide phosphate (NADP) reductase (FNR) from the primary phase of photosynthesis, and the small chloroplast protein, CP12. Sequences of copurified GAPDH and FNR were highly homologous with published sequences. However, the widespread ternary complex among GAPDH, phosphoribulokinase and CP12 was absent. Activity measurements under oxidizing conditions showed that NADPH can inhibit GAPDH‐CP12 in the presence of FNR, explaining the earlier observed inhibition within crude extracts. Diatom plastids have a distinctive metabolism, including the lack of the oxidative pentose phosphate pathway, and so cannot produce NADPH in the dark. The observed down‐regulation of GAPDH in the dark may allow NADPH to be rerouted towards other reductive processes contributing to their ecological success.